Two new secolignans from the roots of Urtica fissa. Issue 2 (1st February 2019) - Lu, Xuan; Li, Xue-Qing; Qin, Hai-Hong; Feng, Bao-Min; Cheng, Xing-Hua; Yang, Qing-Xiong; Yu, Da-Yong; Shi, Li-Ying; Yu, Zong-Xia; Fang, Xue-Xun
Abstract: Two new secolignans, 3, 4- trans -3-hydroxymethyl-4-[bis(4-hydroxy-3- methoxyphenyl)methyl]butyrolactone (1 ) and 3, 4- trans -3-hydroxymethyl-4- [bis(3, 4-dimethoxyphenyl)methyl]butyrolactone (2 ) have been isolated from the roots of Urtica fissa E.Pritz. Their structures were determined on the basis of spectroscopic methods, especially 1 H NMR, 13 C NMR, 2D NMR, and HR-ESI-MS. The inhibitory effects on N1 and N2, two subtypes of neuraminidases (NAs), of these two compounds were assayed. Abstract :